Prototype Data Warehouse Kantor Penilai Publik XYZ Dengan Metode Nine-Step Kimball - Ratu, Anggitta; Kusneti, Leni; Wijaya, Andri (Journal Of Informatics And Busisnes, 2023)
In the era of information technology, data management has become crucial for organizations. The Public Appraisal Office (KJPP) XYZ in Palembang City, despite providing accurate property analysis, is still limited to the use of hard disks, hard copies, email, and Excel. This results in a lack of integration and efficiency in their operations. Therefore, this research proposes a solution in the form of designing a data warehouse prototype using the Nine-Step Kimball method. This method is employed as a systematic approach in designing and building a data warehouse, with the aim of ensuring effective and relevant development for business needs. The design will organize data into table components, creating regularity and centralization of data to facilitate search and analysis. The inspiration for this research comes from similar implementations in online market transactions and television editorial decisions using the snowflake schema and the successful Nine-Step Kimball method. It is hoped that through this approach, KJPP XYZ can optimize access, analysis, and use of the data.